2014
DOI: 10.1186/1471-2253-14-54
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ischemic and pharmacological preconditioning of lower limb muscle tissue on tissue oxygenation measured by near-infrared spectroscopy – a pilot study

Abstract: BackgroundIschemic or volatile anesthetic preconditioning is defined as tissue protection from impending ischemic cell damage by repetitive short periods of tissue exposure to ischemia or volatile anesthetics. Objective of this study was to elucidate, if ischemic preconditioning and pharmacological preconditioning with sevoflurane have effects on muscle tissue oxygen saturation in patients undergoing surgical revascularization of the lower limb.MethodsIn this prospective randomized pilot study ischemic and pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…A single article was identified through review of references. Of the 23 articles, 4 were removed because of being reviews, 1,4,13,14 2 used anesthetic agents only, 15,16 2 were protocols, 17,18 and 2 were not relevant, 19,20 leaving 13 articles for inclusion [21][22][23][24][25][26][27][28][29][30][31][32][33] (Fig 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A single article was identified through review of references. Of the 23 articles, 4 were removed because of being reviews, 1,4,13,14 2 used anesthetic agents only, 15,16 2 were protocols, 17,18 and 2 were not relevant, 19,20 leaving 13 articles for inclusion [21][22][23][24][25][26][27][28][29][30][31][32][33] (Fig 1).…”
Section: Resultsmentioning
confidence: 99%
“…21,24,28 There was also no significant difference in overall length of stay in any study. 21,22,24,28,30,32,33 Heterogeneity. Supplementary Table III (online only) shows heterogeneity statistics for the four outcomes considered.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Animal experiments demonstrated that ischemic preconditioning showed no protective effect in I/R injury when pharmacologic preconditioning (isoflurane or sevoflurane) was administered concomitantly [Vianna 2009;Kuzume 2004]. However, if administered sequentially, it provided synergistic effects [Toller 1999;Fudickar 2014]. Lucchinetti et al [Lucchinetti 2012] reported that RIPC combined with isoflurane administered concomitantly provided no additional benefit to the myocardium and revealed a lack of synergy or evidence of antagonism in cardioprotection in both strategies.…”
Section: E922mentioning
confidence: 99%
“…Это подтверждается не только более низким уровнем специфических маркеров повреждения миокарда, но и снижением в периоперационном периоде частоты осложнений. Ишемическое прекондиционирование севофлюраном оказывает влияние и на оксигенацию тканей у больных с окклюзионными поражениями артерий нижних конечностей [15][16][17][18].…”
Section: результаты исследования и их обсуждениеunclassified